Archive 17 : a novel of suspense - Eastland, Sam. (New York : Bantam Books, 2012)
It's 1939. Russia teeters on the verge of war with Germany. It is also on the brink of bankruptcy. To preserve his regime, Stalin orders a search for the legendary missing gold of Tsar Nicholas II. For this task, he chooses Pekkala, the former investigator for the Tsar. To accomplish his mission, Pekkala will go undercover, returning to Siberia and the nightmare of his own past, where he was once a prisoner in the notorious Gulag known as Borodok and where he must infiltrate a gang of convicts still loyal to the Tsar.
edited hb 2015-06-16
Keywords: Stalin, Joseph, -- 1879-1953 -- Fiction; Treasure troves -- Fiction; Soviet Union -- History -- 1925-1953 -- Fiction; Historical fiction; Suspense fiction